New ostracod species (Cypridopsis schwartzi n. sp.) from Texas, with discussion on the taxonomic status of Cypridopsis species in the USA - Külköylüoğlu, Okan; Veech, Joseph A.; Tuncer, Alaetti̇n (Zootaxa, 2022)
A total of 39 taxa (19 living species, 20 subfossils) were collected from 59 different shallow aquatic bodies in Texas during April to June 2017. Cypridopsis schwartzi n. sp. is proposed as a new species collected from a cattle pond at Freeman Ranch near San Marcos, Texas. The species has several characteristics separating it from other species, including carapace shape, presence of a curved z3-seta on the second antenna, number of setae on the vibratory plate of the first thoracic leg, shape of hemipenis, numbers of whorls on the Zenker organ, and several other differences. With the new species, there are now 12 species in the genus Cypridopsis recorded for Texas, and Cypridopsis schwartzi n. sp. is the fifth species of the genus in Texas showing sexual reproduction. The new species was compared with other species of the genus in Texas and the taxonomic relationships are discussed.